Penjadwalan Penggantian dan Perbaikan Pemeras Tebu Kapasitas 10 kg/Jam Periode 2026 - Muchammad Firman Maulana; Syamsul Hadi; Ahmed Sahlur Rosyad; Muhammad Maulana Yusuf Aditya; Thilal Omar Syarif (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The problem with the sugarcane press machine is a decrease in performance in sugarcane pressing because it has been used since 2020 with an initial price of IDR 3,000,000, which is predicted to be IDR 5,500,000 in 2025 which occurs in the main components of the roler mill, V-belt, and bearings. The purpose of scheduling replacements and repairs is to obtain a schedule, estimated maintenance costs, and the ratio of replacement and repair costs to the profit of renting a sugarcane press for the period 2026. The scheduling method includes collecting data on the use of the sugarcane press machine, a list of replacements for 5 components for roler mills, V-belts, bearings, gasoline motor tanks, and engine frames from 34 components, component prices, estimated labor costs, equipment costs, supporting material costs, application of the inspection, replace, repair, and overhaul (IRRO) method, scheduling replacements and repairs, and calculating the ratio of replacement costs to profits. The results of the replacement and repair scheduling are in the form of maintenance costs of IDR 958,000, with a rate of IDR 10,000/hour for 588 hours/year, resulting in a profit of IDR 5,880,000, and a ratio of maintenance and repair costs to profit of 0.16%.